# Difference between revisions of "Evidence for universal scaling behavior of a freely relaxing DNA molecule"

(→Reference) |
(→Key Results) |
||

Line 16: | Line 16: | ||

</math> | </math> | ||

− | Where L(t) is the length at time t, <math>L_0</math> is the initial length, k is the [[Boltzmann constant]], T is the absolute temperature, <math>\eta</math> is the viscosity of the solvent, and a is the [[persistence length]]. | + | Where L(t) is the length at time t, <math>L_0</math> is the initial length, k is the [[Boltzmann constant]], T is the absolute temperature, <math>\eta</math> is the viscosity of the solvent, and a is the [[persistence length]]. The experiments showed that: |

+ | * <math>L(t)-L_0</math> obeys a power law | ||

+ | * Changing <math>\eta</math> does not change the scaling exponent | ||

+ | |||

+ | All of the experiments can be plotted at the same time if we plot | ||

+ | <math> \frac{L(t)-L_0}{L_0 /2} </math> | ||

+ | versus | ||

+ | <math> \frac{t}{\tau_{1/2}} </math>, where | ||

+ | <math> L(\tau_{1/2}) = L_0/2 </math>. | ||

==Why Care== | ==Why Care== | ||

==Methods== | ==Methods== |

## Revision as of 21:20, 19 October 2009

## Contents

## Reference

**Evidence for the universal scaling behaviour of a freely relaxing DNA molecule**

S. Manneville, Ph. Cluzel, J.-L. Viovy, D. Chatenay, F. Caron

Europhysics Letters **36**: 413-418 (1996)

## Key Results

The Brochard-Wyart "stem-and-flower" model posits that the relaxation of a tethered polymer under flow at intermediate velocities is described by

<math> L(t)-L_0 \propto \sqrt{\frac{kT}{\eta a} t} </math>

Where L(t) is the length at time t, <math>L_0</math> is the initial length, k is the Boltzmann constant, T is the absolute temperature, <math>\eta</math> is the viscosity of the solvent, and a is the persistence length. The experiments showed that:

- <math>L(t)-L_0</math> obeys a power law
- Changing <math>\eta</math> does not change the scaling exponent

All of the experiments can be plotted at the same time if we plot <math> \frac{L(t)-L_0}{L_0 /2} </math> versus <math> \frac{t}{\tau_{1/2}} </math>, where <math> L(\tau_{1/2}) = L_0/2 </math>.